Cu-II-exchanged montmorillonite K10 clay-catalyzed direct carboxylation of terminal alkynes with carbon dioxide - Aher, Ravindra D.; Gade, Madhuri H.; Reddy, R. Santhosh; Sudalai, Arumugam (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
A new, simple and straight-forward protocol for direct carboxylation of terminal alkynes has been developed using Cu-II-montmorillonite K10 clay as a heterogeneous catalyst and CO2 as the C1 carbon feedstock. Also coupling of terminal alkynes with CO2 (1 atm) in the presence of alkyl halides has been achieved under the same reaction conditions, thereby providing access to a variety of functionalized alkyl-2-alkynoates in high yields.
Keywords: Alkyl esters; Alkyne C-H activation; Carbon dioxide activation; Carboxylation; Catalysts; Montmorillonite clays